Width of buccal and posterior corridors: differences between cases treated with asymmetric and symmetric extractions - Nuria Cabral Castello Branco; Guilherme Janson; Marcos Roberto de Freitas; Juliana Morais (Dental Press Editora, 2012)
OBJECTIVE: To verify if there is difference in the buccal and posterior corridor width in cases treated with extraction of one and four premolars. METHODS: Through posed smile photographs of 23 Class II patients, subdivision, treated with extraction of one premolar and 25 Class I and Class II patients, subdivision, treated with extraction of four premolars, the percentage of buccal and posterior corridor width was calculated. The two protocols of extractions were compared regarding the buccal and posterior corridor width by independent t tests. RESULTS: There was no statistically significant difference on the buccal and posterior corridor widths between patients treated with symmetric and asymmetric extraction. CONCLUSION: The buccal and posterior corridor did not differ between the evaluated protocols of extractions. OBJETIVO: verificar se há diferença na largura dos corredores bucal e posterior em casos tratados com extrações de um e quatro pré-molares. MÉTODOS: por meio de fotografias do sorriso posado de 23 pacientes Classe II, subdivisão, tratados com extração de um pré-molar, e de 25 pacientes Classe I, Classe II e Classe II, subdivisão, tratados com extração de quatro pré-molares, calculou-se o percentual da largura dos corredores bucais e dos corredores posteriores. Os dois protocolos de extrações foram comparados quanto à largura dos corredores bucal e posterior por meio do teste t independente. RESULTADOS: não houve diferença estatisticamente significativa na largura dos corredores bucal e posterior entre os pacientes tratados com extrações simétricas e assimétricas. CONCLUSÃO: o corredor bucal e o corredor posterior não diferiram entre os protocolos de extrações avaliados.